Blood Profile, Productivity and Carcass Pieces of Super Superior Kampung Chicken Supplemented with Vitamin C, Vitamin E, Selenium Infected with Escherichia coli - Roisu Eny Mudawaroch; Faruq Iskandar; Fayza Maya Azzahra; Ushonahito Muhammad Rizquna (Postgraduate, University of Mataram, 2026)
Balitbangtan's superior native chicken (KUB) is a local chicken produced from genetic crossbreeding of native chickens that are susceptible to heat stress. Heat stress was reduced by adding vitamin C, vitamin E, and Se to the feed. The purpose of this study was to determine the effect of supplementation of Vitamin E, Vitamin C, and Se in KUB chickens on blood profiles, productivity, and carcass cuts. The materials used were KUB chickens, Vitamin C, Vitamin E, and selenium. This study used a completely randomized design with 6 treatments and 5 replications. The results showed that supplementation of vitamin E, Vitamin C, and selenium in chickens infected with Escherichia coli did not show significant differences in drinking consumption and body weight but showed differences in feed consumption. Meanwhile, long-term maintenance had a significant effect. Supplementation of vitamin E, Vitamin C, and selenium in chickens infected with Escherichia coli did not show significant differences in carcass and carcass cuts. Blood protein, hemoglobin, red blood cells, hematocrit, monocytes, basophils, neutrophils, and lymphocytes did not show any differences, while eosinophils showed significant differences with the treatment of supplementation of vitamin E, Vitamin C, and selenium in chickens infected with Escherichia coli. The conclusion of this study is that supplementation of vitamin E, Vitamin C, and selenium in chickens infected with Escherichia coli did not show any differences in productivity, carcass, and blood profile, but had a significant effect on feed consumption and eosinophils.